Community-Based Research in Fragile Contexts: Reflections From Rohingya Refugee Camps in Cox's Bazar, Bangladesh. (March 2023) - Hoque, Mohammad Azizul; Ahmad, Tasnuva; Manzur, Samira; Prova, Tasnia Khandaker
This commentary examines community-based research in fragile settings based on the authors' experience working with Rohingya and host community researchers in Cox's Bazar, Bangladesh. This iteration of a community-based approach to research focuses on putting community researchers at the center and emphasizes their involvement at each stage of the research process – from design to implementation to analysis – alongside external researchers. Community researchers contribute their expertise to increase understanding of nuances that might otherwise be lost to external researchers. Integral to this approach is building and nurturing the trust of researchers, respondents and community members through innovative means such as an informal "trust network." Also central to the community-based approach, especially in fragile 1 settings, is a sustained emphasis on community researchers' learning and skills-building. The commentary article describes methods developed by the Centre for Peace and Justice, Brac University (CPJ), implemented with Rohingya refugees and host community researchers in Cox's Bazar. The article suggests: Putting community members at the heart of learning and research approaches helps to amplify marginalized voices and emphasize their needs and choices. The political and economic atmosphere of a refugee setting can change rapidly. In such circumstances, community-based research can be vital to policymakers that seek to understand emerging concerns and issues. Community-based experiential education and research approaches hold potential to promote grassroots leadership among refugee youth in situations of protracted displacement. Strengthening the capacities of community researchers is crucial to this approach. Community researchers often lack language skills, especially writing and reading, and translating from local dialects to English or any other preferred language. The acquisition of research skills can also pave a durable and critical pathway toward meaningful youth engagement. Trust and familiarity between refugee interlocutors and researchers require long-term engagement. Creating a culture of mutual respect and dignity is of utmost importance. The community expects researchers to respect their religious beliefs and cultural values. The two-way exchange between community researchers and respondents enhances the learning process and can help discover areas for further inquiry.